Using molecular dynamics simulation to examine the evolution of blood barrier structure in the presence of different electric fields - Baydaa Abed Hussein; Ibrahim Saeed Gataa; Abrar A. Mohammed; Soheil Salahshour; Sh. Baghaei (International Journal of Thermofluids)
Membrane disruption refers to increasing cell membrane permeability. This state may be transient, allowing the cell to regain its function, or it can be lasting, resulting in the cell's demise. Disrupting the membrane can momentarily affect the blood-brain barrier, making drugs easier to penetrate. This research aimed to investigate issues related to the blood-brain barrier that resulted from irreversible membrane disruption, using computer simulations. This study investigated how changing electric fields affected things like the blood-brain barrier's cross-sectional area, gyration radius, mean square displacement, heat flux, electric current density, and how the electric field was distributed in the blood-brain barrier. The simulations were conducted to adjust and modify the final structure. During the initial phase of equilibration, simulations were conducted for 10–8 s, leading to the stabilization of the kinetic energy and potential energy of the initial atomic sample at specific values. As the electric field amplitude increased, the radius of gyration in the blood barrier also increased, reflecting enhanced molecular motion. Specifically, it increased from 32.79 to 33.30 Å when the amplitude increased from 0.1 to 0.6 eV This increased motion was due to larger oscillation ranges and intensified interatomic collisions, leading to a higher mean squared displacement of 27.37 nm² at 0.6 eV Additionally, the heat flux within the blood barrier increased to 0.0072 W/m², indicating that stronger electric fields induced more erratic molecular behavior.